2016
DOI: 10.1016/j.bjid.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic-driven antifungal therapy in neutropenic patients using the D-index and serial serum galactomannan testing

Abstract: A risk stratification using D-index was a useful instrument to be incorporated in invasive mold disease diagnostic approach, resulting in a more comprehensive antifungal treatment strategy, and to guide an earlier start of treatment in afebrile patients under very high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…They have reported that the c-D-index cutoff value of ≥5,500 is a sensitive predictor of IFI [ 7 ]. This original report was followed by further studies in this area [ 20 , 21 ]. In both reports, a 9–10-day period of prolonged neutropenia was associated with a high risk of IFI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have reported that the c-D-index cutoff value of ≥5,500 is a sensitive predictor of IFI [ 7 ]. This original report was followed by further studies in this area [ 20 , 21 ]. In both reports, a 9–10-day period of prolonged neutropenia was associated with a high risk of IFI.…”
Section: Discussionmentioning
confidence: 99%
“…Some advances have been made in the sensitive and accurate diagnosis of infections [ 23 ]. The development of these medical techniques and procedures will establish an easier approach to empirical and presumptive diagnosis-driven antimicrobial therapy [ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the inappropriate conditions for AML treatment, higher incidence of bacterial and fungal infections is frequently reported. These inappropriate conditions could be associated to the tropical climate, lack of enough beds in rooms with positive-pressure laminar flow, and difficulties in the access to the workup for invasive mold disease [48]. Neutropenic fever (NF) is a very common complication during induction therapy and even after consolidation.…”
Section: Barriers To Access To Therapy In Developing Countriesmentioning
confidence: 99%
“…In a follow-up prospective study among 29 patients with acute leukemia undergoing remission-chemotherapy, the investigators utilized the D-index and galactomannan screening to stratify patients as low (<3000), intermediate (3000–5800), and high risk (>5800) for IMD [87]. Although a positive galactomannan result or clinical symptoms triggered a diagnostic workup in similar numbers of patients irrespective of the D-index risk stratification (58–73%), patients in the low risk D-index group were less likely to receive antifungal therapy (17% vs. 54–67%) and no cases of IMD were diagnosed in the low risk group versus 67% and 45% of the patients classified as high and moderate risk, respectively.…”
Section: Risk Models For Invasive Mold Diseasementioning
confidence: 99%